1979
DOI: 10.1203/00006450-197901000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of Amino Acid Reabsorption in Human Kidney. Evidence from the Homozygous Infant with Familial Renal Iminoglycinuria for Multiple Proline and Glycine Systems

Abstract: Summaryadditional transport process(es) in the renal tubule, perhaps one with a preference for iminoacids and another with preference for seven infants French Canadim9' Our J e~s h , glycine (16,24). Since net reabsorption is determined to a great and one Greek) with massive selective hyperiminoglycinuria (proline, hydroxyproline, and glycine) were detected by urine screening extent by brush border membrane transport activity of the proxiin the second week of life. Follow-up investigations and family ma1 tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Total RNA was isolated from rat tissues using TRIzol reagent (Invitrogen) according to the manufacturer's protocol. For reverse transcription, 0.5 g of oligo(dT) [12][13][14][15][16][17][18] and 1 l of dNTPs (10 mM) were added to 1 g of total RNA in a total volume of 10 l. The mixture was incubated for 10 min at 65°C and then chilled on ice. Dithiothreitol (2 l, 0.1 M), 10ϫ reverse transcriptase buffer (2 l), MgCl 2 (4 l, 25 mM), and 40 units of RNaseOUT (Invitrogen) were added, and the mixture was incubated at 42°C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Total RNA was isolated from rat tissues using TRIzol reagent (Invitrogen) according to the manufacturer's protocol. For reverse transcription, 0.5 g of oligo(dT) [12][13][14][15][16][17][18] and 1 l of dNTPs (10 mM) were added to 1 g of total RNA in a total volume of 10 l. The mixture was incubated for 10 min at 65°C and then chilled on ice. Dithiothreitol (2 l, 0.1 M), 10ϫ reverse transcriptase buffer (2 l), MgCl 2 (4 l, 25 mM), and 40 units of RNaseOUT (Invitrogen) were added, and the mixture was incubated at 42°C for 2 min.…”
Section: Methodsmentioning
confidence: 99%
“…Kidney-Newborn rodents and man exhibit a marked hyperexcretion of proline that disappears within a few days, 1 week, 1 month, or 3 months after birth in rat, dog, and man, respectively (13,44,45). Studies using rat renal brush-border membrane preparations suggested that the proline hyperexcretion results from depressed Na ϩ -dependent proline reuptake in the neonate (3,44,46).…”
Section: Onset Of Sit1 Expression In the Neonate Can Account For The mentioning
confidence: 99%
See 2 more Smart Citations
“…In the absence of controlled prospective studies of IG and HG cohorts, some of these associations may represent ascertainment bias. Based on detailed biochemical studies in 7 families, Lasley and Scriver (19) suggested that 3 genes account for imino acid and glycine reabsorption in the kidney proximal tubule, namely a common transporter for both types of amino acids and a specific transporter each for glycine and imino acids. This model of 1 common and 2 specific transporters is well supported by transport studies in intact tubules, brush-border membrane vesicles, and cell lines from a wide variety of organisms (20).…”
Section: Introductionmentioning
confidence: 99%